Participation and health care provision of statutory skin cancer screening in Germany – a secondary data analysis. (9th February 2016) - Anastasiadou, Z.; Schäfer, I.; Siebert, J.; Günther, W.; Reusch, M.; Augustin, M.
Abstract: Background: In Germany, skin cancer screening was introduced nationwide in July 2008. From the age of 35 years, members of the statutory health insurance are eligible for screening every 2 years. Objective: The aim of this study is to calculate the participation rates and the proportions of health care providers of statutory skin cancer screening in Germany on a population‐based level. Methods: Data were provided by a nationwide German statutory health insurance, approximately 6.1 million members, covering the years 2008/2009. Participation rates were calculated per yearly quarter and were adjusted for age, gender and federal state. Results: Approximately 920 000 insurants were screened from the third quarter of 2008 until the last quarter of 2009. Mean participation rate of skin cancer screening was 30.8%. Women had higher participation rates (31.9%) than men (29.7%). After adjusting for gender and federal state, high rates for pensioners at the age of 65–74 were confirmed at 39.4% on average for all yearly quarters. One of the highest gender‐ and age‐adjusted rates was observed in the state of Schleswig‐Holstein, where a population based pilot project had been implemented before the start of the nationwide screening programme. In general, without taking into account Berlin, former East Germany had a much lower gender‐ and age‐adjusted participation rate (23.9%) than West Germany (33.3%). At the first quarter after implementation of screening, 58.5% of the screenings were provided by dermatologists and 41.5% by general practitioners. Conclusion: Participation rates and health care providers of skin cancer screening can be calculated from secondary data and contribute to identify group‐ and region‐specific participation patterns in order to improve early detection of skin cancer.